PENGARUH INCOME DAN FINANCIAL KNOWLEDGE SERTA LOCUS OF CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR - Luh Intan Rini Andriyani; Wayan Cipta (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to take the results of findings that have been through the test process related to the influence both partially and simultaneously of income, financial knowledge, and locus of control on financial management behavior. The type of research that is raised quantitatively. Private employees in sangsit village were the subject of the study, while income, financial knowledge, and locus of control of financial management behavior were the objects. Before being analyzed using multiple linear regression analysis, data collection is done first utilizing the spread with questionnaires. It's quantitatively causal. So that the results of the test process that (1) financial management behavior is positively influenced significantly by income, financial knowledge, and locus of control of financial management behavior. (2) Financial management behavior is positively affected by income. (3) Financial management behavior is not significantly affected by financial knowledge. (4) Financial management behavior is positively affected significantly by the locus of control.